Pengaruh Ulasan Pelanggan, Kredibilitas Infleuncer, Ulasan Influencer terhadap Niat Beli dnegan Peran Moderasi Kepercayaan - Purwanto, Kayla Azzura Putri; Astuti, Budi (Universitas Hamzanwadi, 2024)
Electronic commerce transactions have rapidly evolved due to advancements in internet technology. In today's digital era, online purchasing has become a significant global trend, particularly in Indonesia. The e-commerce platform Shopee has emerged as one of the most popular among consumers. This study aims to assess the influence of customer reviews, influencer credibility, and influencer reviews on purchase intention, considering the moderating role of trust. The research methodology employed a quantitative approach using purposive sampling techniques, involving 230 respondents. The findings indicate that influencer credibility, influencer reviews, and trust positively affect purchase intention, while customer reviews do not have a significant impact. Additionally, trust does not moderate the relationship between these factors. The conclusion drawn from this study is that influencer credibility, influencer reviews and trust play crucial roles in enhancing purchase intention among customers towards the Saff & Co brand through the Shopee e-commerce platform